Case Studies On Women Entrepreneurs In Delhi Ncr: A Deep Dive Into The Growth And Impact Of Female-Driven Businesses (International Journal of Environmental Sciences, 2025)
Purpose This study explores the evolving landscape of women entrepreneurship in Delhi NCR, a region witnessing rapid economic growth driven by female-led ventures. It aims to identify the challenges faced by women entrepreneurs and the opportunities available to build a more inclusive entrepreneurial ecosystem.MethodologyThe research is based on a mixed-methods approach, combining secondary data analysis, literature review, and 13 in-depth case studies from diverse sectors such as e-commerce, fintech, wellness, consulting, and social entrepreneurship in the Delhi NCR region.FindingsThe study highlights key barriers including socio-cultural expectations, limited access to finance, and restricted networking opportunities. Despite these challenges, digital platforms, government initiatives like Stand-Up India and state-level programs, as well as access to mentorship and technology, have empowered women entrepreneurs to scale their businesses and create impact.Practical ImplicationsThe paper offers actionable policy recommendations to improve financial access, promote mentorship, integrate entrepreneurship into education, and reduce gender bias. These insights are useful for policymakers, investors, and business leaders working toward inclusive growth.LimitationsThe study relies on secondary data, which may not fully reflect current ground realities or micro-enterprise perspectives.Originality/ValueBy focusing on Delhi NCR, this paper offers a region-specific analysis combining policy, innovation, and real-world case studies to support gender-inclusive entrepreneurship